DEVELOPMENT OF FATWA CONTEMPORARI IN ACCEPTING GLOBALIZATION CHALLENGES: ONE APPROACH - Prof. Madya Dr. Alias bin Azhar; Dr Mohammad Azam Bin Hussain (Journal of Islamic, Social, Economics and Development, 2017)
Globalization is a worldwide cultural reform that affects all walks of life. Although originally directed toward openness in world economic activity, but has now begun to include openness and change in the political, social and social aspects of society. The diversity of these issues is the immediate impact of globalization is the drastic development of the revolution and the evolution of science and technology. The uniqueness of the relationship between revelation and reason and understanding is that it ensures that fatwa research is always superior and capable of responding to current issues. The objective of the fatwa research actually exists as closely related to the Shariah objective (Maqasid al-Syariah) itself. The fiqh research is based on two main frameworks which can not be separated from one another. First is the revelation of Allah whose truth is mutlaq and muqaddas, as found in the Qur'an and al-Sunnah. The first framework of revelation requires a human understanding in responding to and interpreting its meaning. On this basis is the jurisprudence and conducting fiqh research efforts extensively and effectively. The study expects three (3) main methods ie content analysis that examines the framework of fatwa epistemology and ijtihad in Islam (question of the source, the nature of a science and the balance sheets) used by a scholar / Syariah scholar; historiography and comparative methods that examine the history of the construction of Islamic law and sociological research methods that examine the background of societies such as socio-political aspects, structures, economics and certain institutions (such as the impact of globalization) that affect the income of the fatwa. Discussion of this article covers the concept and approach of fiqh maqasidi research and scientific fiqh in the context of fatwa development to meet the challenges of globalization. People are now faced with many new issues, the impact of the changing patterns of life and the rapid development of science and technology, as well as the birth of an era known as the Cyrene era in a broad framework called globalization. Fatwa institutions need to carry out legal affairs through fatwa research in two fiqh research frameworks ie fiqh maqasidi and scientific fiqh. Only in such a way that fatwa research results are able to meet the challenges of today and take precedence over all developments that take place in the face of globalization challenges.